Business Intelligence In Healthcare Industry (International Journal of Engineering and Computer Science, 2022)
Nowadays Business Intelligence applications are trending in different fields such as Healthcare, LifeSciences, ERP, Marketing, Retail, food industry, travel and transport industry etc. This paper mainly focuses on how we can use different ETL functionalities in order to ease the daily routine task used in different healthcare industries.